Nanostructured lipid carriers-hydrogels system for drug delivery: nanohybrid technology perspective - Syed Azhar, Sharifah Nurfadhlin Afifah; Ashari, Siti Efliza; Zainuddin, Norhazlin; Hassan, Masriana (Multidisciplinary Digital Publishing Institute, 2022)
Advanced hybrid component development in nanotechnology provides superior functionality in the application of scientific knowledge for the drug delivery industry. The purpose of this paper is to review important nanohybrid perspectives in drug delivery between nanostructured lipid carriers (NLC) and hydrogel systems. The hybrid system may result in the enhancement of each component’s synergistic properties in the mechanical strength of the hydrogel and concomitantly decrease aggregation of the NLC. The significant progress in nanostructured lipid carriers–hydrogels is reviewed here, with an emphasis on their preparation, potential applications, advantages, and underlying issues associated with these exciting materials.